Conceptual Study on Action of Visha Gunas with Snake Venom Compounds- A Comparison (International Journal of Ayurveda and Pharma Research, 2023)
Ayurveda, an Upaveda of Atharvaveda emphasis on the prevention of disease and yield positive health through proper diet, healthy lifestyle, right thinking with pleasant mind along with use of right choice of drugs, in short, a proper balance between body, mind and senses. Ayurveda deals mainly with eight branches of special units. Agadatantra (toxicology) is one among them and a most special wing for the diagnosis and management of different kinds of animate and inanimate poisoning. Visha (poison) is a substance imbalance the healthy constitution of the body and destructs the life by its different Gunas (properties). The qualities of Visha determine the lethality. In ancient Ayurvedic literature different opinion regarding the qualities of Visha. Each attribute has different action inside the body. The snake venom is highly toxic and contains more than 20 different compounds mainly include proteins and polypeptides. These mixtures of proteins, enzymes and other co factors determine toxicity and fatality, in correspondence with Teekshnadi Gunas of Visha. This article made an attempt to compare the Visha Guna action with that of snake venom compounds.